Ensayo de rendimiento de dos variedades de papa y fríjol en asociación, con diferentes poblaciones. - Zandstra C, Hubert G.; Rey A, Guillermo (Instituto Colombiano Agropecuario, 2018)
Fríjol-Phaseolus vulgaris